Investigating the Mediterranean diet's role in Alzheimer's disease prevention: a review - Meshram, Anju; Yadav, Dhananjay; Song, Minseok (Progress in Nutrition, 2023)
Alzheimer's disease (AD) is the highest predominant style of dementia, is a neurological disorder that worsens over time and has no known treatment. AD research is paying more and more attention to lifestyle factors, including diet and nutrition. The Mediterranean diet (MeDi) may offer defence against dementia and cognitive deterioration, according to some research. According to various epidemiological studies, people who follow a MeDi have a lower risk of developing cognitive problems. Higher MeDi adherence was linked to a lower likelihood of incident cognitive impairment, whereas lower adherence was linked to a rise in AD and mild cognitive impairment. Progressive AD biomarker abnormalities have been linked to lower MeDi adherence in middle-aged adults. Reduced vascular risk factors and favourable effects on glucose and lipid metabolism may also contribute to the MeDi's lower risk of AD. The MeDi may have preventive effects against cognitive decline, including AD, because to some of its components, including its high fruit and vegetable content, relatively low level of carbs, and usage of added-virgin olive oil as the primary basis of fat. However, other aspects of the Mediterranean lifestyle, such consistent exercise and robust social networks, might help lower the risk of the illness. To prove a link between MeDi and the prevention or amelioration of cognitive loss in AD, long-term randomised controlled trials are required. Since it is unknown what specific food components and bioactives are needed for efficient neuroprotection, it is currently not practical to prescribe the MeDi as a preventive measure in AD. According to the available evidence, the MeDi should be implemented as part of public health initiatives aimed at lowering the risk of AD. To prove a link between MeDi and the prevention or amelioration of cognitive loss in AD, however, long-term randomised controlled trials are required.